Major Women Empowerment Initiatives in Balochistan: A Critical Review and Policy Recommendations - Ijaz, Asma (Journal of Pakistan Administration, 2024)
This policy paper critically reviews major initiatives undertaken in the province of Balochistan regarding women empowerment, focusing on both government and non-governmental interventions, specifically, aimed at the reduction of gender disparities in education, healthcare, and economic participation. Despite ongoing efforts such as the Balochistan Rural Support Program (BRSP), Balochistan Education Endowment Fund (BEEF), and the Benazir Income Support Program (BISP), women in Balochistan continue to face substantial socio-economic challenges due to high illiteracy rates, poverty, lack of access to quality healthcare, and limited political representation. This study identifies the key barriers to empowerment, including entrenched patriarchal norms, early marriage, and economic marginalization. The research highlights the need for a multidimensional approach to addressing these issues, emphasizing the importance of educational, economic, and health empowerment initiatives. Furthermore, the policy paper suggests a set of recommendations such as skill training programs, enhanced educational access, microfinancing initiatives, and healthcare facilities to foster women’s participation in societal development. The implementation of these initiatives, however, requires robust legal frameworks and collaboration between government, NGOs, and community leaders.